PEST POPULATION OF Spodoptera frugiperda J.E.SMITH (Lepidoptera: Noctuidae) ON CORN PLANTATION IN LOLAK DISTRICT, BOLAANG MONGONDOW REGENCY. - Dian Liput; Betsy A.N. Pinaria; Caroulus S. Rante; Noni N. Wanta (Jurnal Agroekoteknologi Terapan, 2022)
This study aims to determine the population of S. frugiperda pests in corn plantations in Tuyat and Tandu Villages, Lolak District, Bolaang Mongondow Regency. The results of the study are expected to provide information about the presence of the pest population of S. frugiperda, so that it can assist in developing further control strategies.  The study used a survey method, namely by making direct observations at the research location. The maize varieties observed were BISI 2 grown by farmers in Tandu Village and BISI 18 in Tuyat Village. The age of the plant was in accordance with field conditions and sampling was done intentionally at two locations, namely in Tuyat and Tandu Villages. Before making observations, a survey of the research site was conducted as a place to collect data on the population of S. frugiperda pests. The research location is based on corn planted area with a minimum area of ± 0.5 ha in two different places, namely in Tuyat and Tandu Villages. After determining the location, the next step is to determine the sampling pattern, namely by setting a size of 5 x 5 meters in each subplot (each plot consists of ± 70-80 plants). Observations were made once a week for three weeks with sampling 3 times. The number of sample plants observed was 300-400 corn plants at each location. The number of population and affected plants were counted and then recorded at each observation.  The results of the study found that the average larval population varied in each village. The average larval population in the first, second and third weeks in Tandu Village, respectively, was 12.4, 9.8, and 4.2 individuals, which was relatively higher than the average larvae in Tuyat Village, respectively, namely 4.2, 11.8, and 5.8 individuals.Keywords : Population, Spdoptera frugiperda, Bolaang Mongondow RegencyAbstrakPenelitian ini bertujuan untuk mengetahui populasi hama S. frugiperda pada pertanaman jagung di Desa Tuyat dan Desa Tandu Kecamatan Lolak Kabupaten Bolaang Mongondow.  Hasil penelitian diharapkan dapat memberikan informasi tentang keberadaan populasi hama S. frugiperda, sehingga dapat membantu dalam menyusun strategi pengendalian selanjutnya.  Penelitian menggunakan metode survei yakni dengan melakukan pengamatan secara langsung di lokasi penelitian.  Varietas jagung yang diamati adalah BISI 2 yang ditanam oleh petani di Desa Tandu dan BISI 18 di Desa Tuyat.  Umur tanaman sesuai dengan kondisi lapangan dan pengambilan sampel secara sengaja di dua lokasi yakni di Desa Tuyat dan Desa Tandu. Sebelum melakukan pengamatan, terlebih dahulu dilakukan survei lokasi penelitian sebagai tempat pengambilan data tentang populasi hama S. frugiperda. Lokasi penelitian adalah berdasar pada areal pertanaman jagung dengan luas minimal ± 0,5 ha pada dua tempat berbeda yaitu di Desa Tuyat dan Desa Tandu.  Setelah dilakukan penentuan lokasi, selanjutnya menetapkan pola pengambilan sampel yakni dengan menetapkan ukuran 5 x 5 meter pada setiap subplot (setiap plot berjumlah ± 70-80 tanaman).  Pengamatan dilakukan setiap satu minggu sekali selama tiga minggu dengan pengambilan sampel sebanyak 3 kali. Banyaknya tanaman sampel yang diamati yaitu 300 – 400 tanaman jagung pada masing-masing lokasi.  Jumlah populasi dan tanaman yang terserang dihitung kemudian dicatat pada setiap pengamatan.  Hasil penelitian ditemukan rataan populasi larva bervariasi pada masing-masing Desa.  Rataan populasi larva pada minggu pertama, kedua dan ketiga di Desa Tandu secara berurutan yakni 12.4, 9.8, dan 4.2 individu yang relatif lebih tinggi dibanding rataan larva di Desa Tuyat secara berurutan yakni 4.2, 11.8, dan 5.8 individu.Kata Kunci : Populasi, Spdoptera frugiperda, Kabupaten Bolaang Mongondow